Investigation of the pharmacological treatment patterns of Chinese patients with major depressive disorder under real-world settings using multi-channel sequence analysis - Wu, Tao; Dong, Sijia; Yang, Lu; Qiu, Hong; Qiu, Hong; Mellor, David; Chen, Jun; Xu, Yifeng (Frontiers in Psychiatry, 2023)
Background: Despite many treatment guidelines available now, the treatment patterns of major depressive disorder (MDD) in China haven’t been well understood due to complexity and diversity. Aim: To describe treatment patterns of MDD patients under real-world settings using electronic health records from a major psychiatric hospital in China. Methods: MDD patients (18-65 years, ICD-10: F32.x, F33.x) newly initiated single antidepressant (AD) in 2015 were enrolled, the date of first AD prescription during study period was defined as index date, and eligible patients were followed up to 1 year. Treatment patterns were revealed and analyzed using multi-channel sequence analysis (MCSA), considering patients’ chronological sequences (in days) of AD prescription, cumulative treatment step(s), and polypharmacy usage during the follow-up. Results: This study (n=5003) identified four types of MDD treatment patterns. The first type (1-time treatment) represents the largest proportion of patients (73.6%, n=3686), followed by the second type (6-month consistent treatment) and third type (long-term, consistent treatment) collectively accounted for 20.6% (n=1031) of patients, by contrast the last type (long-term, inconsistent treatment) made up the rest 5.7% (n=286) of patients while exhibiting the most complicated treatments patterns. The choice of AD was dominated by selective serotonin reuptake inhibitors (SSRIs), while treatment duration spent in polypharmacy spanned at 2.8%, 16.4%, 2.0%, and 36.5% over the 4 types, respectively. Conclusion: Treatment patterns reflecting real-world pharmacological treatment practices of MDD in China were revealed using MCSA. The observed discrepancies between real-world practice and treatment guidelines provided additional insights in improving the clinical management of MDD.